Bringing Radiation Exposures and Associated Health Risks into Perspective—Development of an App. Issue 1 (July 2020) - Abend, Michael; Stricklin, Daniela; Flaig, Nicole; Badie, Christophe; Drouet, Michel; Foster, Crawford; Janiak, Marek K.; Kuipers, Tjerk; Lista, Florigio; Nowosielska, Ewa M.; Riccobono, Diane; de Sanctis, Stefania; et al.
Abstract : Abstract: The NATO HFM 291 research task group (RTG) on "Ionizing Radiation Bioeffects and Countermeasures" represents a group of scientists from military and civilian academic and scientific institutions primarily working in the field of radiobiology. Among other tasks, the RTG intends to extend their work on risk estimation and communication to bridge the gap in appropriate judgment of health risks given a certain radiation exposure. The group has no explicit psychological background but an expertise in radiobiology and risk assessment. The group believes that, as one of the essential first steps in risk communication, it is required to put radiation risk into perspective. Radiation risk requires a weight in comparison to already-known risks. What we envision is to C ompare R adiation exposure-associated health Ris ks (CRRis App) with daily life health risks caused by other common exposures such as cigarette smoking, driving a car, etc. Within this paper, we provide (1) an overview of health risks after radiation exposure, (2) an explanation of the task and concept of an envisioned CRRis App, (3) an overview of existing software tools related to this issue, (4) a summary of inputs and discussions with experts in the field of radiation protection and risk communication during the ConRad conference, and finally, (5) identification of the next steps in the development of the App.